Любовь в седьмом вагоне: [рассказы] / Ольга Славникова - Славникова Ольга Александровна (АСТ, Астрель, 2010)
Экземпляры: ф. 3 (20120627) / Инвентарный номер: 98811 / Цена: 440.59 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 47 / ББК: 84(2Рос=Рус)6